ANALISIS STRATEGI PENGEMBANGAN USAHA DALAM MASA ERA DIGITAL PADA UMKM CAFE SHAN’S JUICE KARAWANG - Rini Nurhasanah Sujana; Sungkono (JOURNAL SAINS STUDENT RESEARCH, 2024)
Shan's Juice Micro, Small and Medium Enterprises (MSMEs) Shan's Juice is included in the culinary of beverages. In fact, this company faces difficulties in developing its business to remain competitive. In order for industrial operations to run well, strategic planning for business development must be made. Descriptive quantitative methods are used in this study to evaluate strengths, weaknesses, opportunities, and threats (SWOT). Once the SWOT analysis is complete, Market development strategies can be used to attract new consumers.